Identifying chemical entities on literature:a machine learning approach using dictionaries as domain knowledge - Grego, Tiago Daniel Pereira, 1983- (2013)
Tese de doutoramento, Informática (Bioinformática), Universidade de Lisboa, Faculdade de Ciências, 2013